A rare case of a male child with post-zygotic de novo mosaic variant c.538C > T in MECP2 gene: a case report of Rett syndrome - Jhanvi Shah (BMC, 2021)
Abstract Background Rett syndrome (RTT) is characterized by a normal perinatal period with a normal head size at birth followed by normal development for the first 6 months of life followed by gradual deceleration of head growth, loss of acquired purposeful hand skills, severe expressive and receptive language impairment, severe intellectual disability and gait and truncal apraxia/ ataxia. It is caused due to mutations in the MECP2 gene and follows an X-linked dominant mode of inheritance. It was observed exclusively in females and was believed to be lethal in males. In contrast to this belief, several males were identified with RTT upon genetic analysis, however, most males expired by the age of 2 years due to neonatal encephalopathy. The ones that survived beyond the age of 2 years, were attributed to the presence of an extra X chromosome (co-occurrence of Klinefelter and RTT) or the ones having mosaic cell lines. Only 11 males with somatic mosaicism are known till date. Case presentation This case reports an ultra-rare case of a male affected with RTT surviving beyond the age of 2 years due to post-zygotic de novo somatic mosaicism. He was identified with a known pathogenic variant c.538C > T (p.R180*), which to the best of our knowledge is exclusively seen in females and has never been reported in a male before. Conclusion The present case is the first report of a mosaic male affected with RTT from India. The present report also carried out genotype-phenotype correlations across surviving mosaic males with RTT. We also postulate the effect of variant type, position along the gene and the variant allele fraction in different tissue types to be correlated with disease severity.